Analysis of Hygiene and Sanitation Practice Within Hospital Foodservice Employees. a Case Study in a Private Hospital in Yogyakarta - Oldriana Prawiro Hapsari; Iman Permana; Ekorini Listiowati (Universitas Muhammadiyah Yogyakarta, 2018)
Hospitals are expected to provide service according to the accreditation committee standard. One of the accreditation criteria is Infection and Prevention Control, in which the hospital must minimalize infection risk from the provided facilities such as hospital food service. Analyzing food handlers hygiene and sanitian practice in PKU Muhammadiyah Gamping Hospital’s Food Service Unit. The research method is a qualitative method, and the design is a case study. Subjects of the research are 13 food handlers, one food service unit supervisor, one sanitation unit supervisor, one infection and prevention control unit, supervisor. Here we conducted a questionnaire to measure knowledge, an observation checklist to observe food handlers compliance and an in-depth interview for their perspective on hygiene and sanitation practice. Food handlers perspective in hygiene and sanitation practice, on knowledge wise 10 (76,92%) food handlers have good knowledge on hygiene and sanitation. 13 (100%) food handlers have a good practice and compliance on practicing food safety and hygiene and sanitation practice. The Conclusion and Advice there are some adversities such as neglection to wear personal protective types of equipment and some facilities need to be upgraded.